2009
DOI: 10.1037/a0014648
|View full text |Cite
|
Sign up to set email alerts
|

The role of cue–target translation in backward inhibition of attentional set.

Abstract: Backward inhibition (BI) refers to a reaction time cost incurred when returning to a recently abandoned task compared to returning to a task not recently performed. The effect has been proposed to reflect an inhibitory mechanism that aids transition from one task to another. The question arises as to precisely what aspects of a task may be inhibited and when the process takes place. Recent work has suggested a crucial role for response-related components of the task, which occur late in the typical trial struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
79
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 44 publications
13
79
0
Order By: Relevance
“…There was also a main effect of Response Repetition, with shorter RTs to response repetitions (878ms) than to response switches (909ms), F (1, 65) = 24.53, p<.001, η 2 G = .006. Replicating previous work Houghton et al, 2009), there was a significant interaction of Cue-Type and Task Sequence [F (1, 65) = 15.85, p<.001, η 2 G = .003], with smaller n-2 task repetition costs for the more "transparent" arrow cues (22ms) than for the more "non-transparent" shape cues (68ms 004. ]: n-2 repetition costs were smaller for response repetitions (20ms) than for response switches (70ms).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…There was also a main effect of Response Repetition, with shorter RTs to response repetitions (878ms) than to response switches (909ms), F (1, 65) = 24.53, p<.001, η 2 G = .006. Replicating previous work Houghton et al, 2009), there was a significant interaction of Cue-Type and Task Sequence [F (1, 65) = 15.85, p<.001, η 2 G = .003], with smaller n-2 task repetition costs for the more "transparent" arrow cues (22ms) than for the more "non-transparent" shape cues (68ms 004. ]: n-2 repetition costs were smaller for response repetitions (20ms) than for response switches (70ms).…”
Section: Resultssupporting
confidence: 78%
“…For example, the current work has implications for our previous line of research focussing on the effects of cue-transparency on the n-2 task repetition cost Grange & Juvina, 2015;Houghton et al, 2009). Our previous work has shown consistently that reducing the transparency of the cue-task relationship increases the n-2 task repetition cost.…”
Section: Theoretical Implicationsmentioning
confidence: 90%
“…Likewise, abolishing the need for response selection by introducing no-go trials (Schuch & Koch, 2003) or reducing the overlap of response-sets across the different tasks (Gade & Koch, 2007) both reduced the n-2 task-repetition costs to a non-significant level. In a related vein, task competition (and hence n-2 task-repetition costs) can also be reduced by facilitating task selection with spatial cues (Arbuthnott, 2005;Arbuthnott & Woodward, 2002) or by increasing cuetarget overlap (Houghton, Pritchard, & Grange, 2009). Taken together, these findings have led to the suggestion that inhibition of abandoned task-sets is used when the degree of competition between tasks is high.…”
mentioning
confidence: 88%
“…In this instance, no n-2 repetition cost is predicted, as no inhibition of WM representations has occurred. Across several studies, reduced n-2 repetition costs with relatively transparent cues compared to relatively less transparent cues have been reported , 2010bHoughton et al, 2009). …”
mentioning
confidence: 99%
“…In their article, Koch et al (2010) review evidence from their laboratory that suggests inhibition targets response stages of task performance (e.g., response preparation/execution). They also review evidence that suggests inhibition may be more flexible, targeting those aspects of the task structure that generate the greatest inter-trial conflict when a task switches (Houghton, Pritchard, & Grange, 2009); indeed, research has shown that cue-based preparatory stages of task performance can be the target of inhibition , 2010bHoughton et al, 2009). Specifically, using a target detection paradigm, Houghton et al proposed that on the basis of the task cue, a relevant target representation must be activated in working memory (WM), a process they called cue-target translation.…”
mentioning
confidence: 99%